2017
DOI: 10.1016/j.icarus.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on water sublimation from 24 Themis and 1 Ceres

Abstract: Recent observations have suggested that there is water ice present on the surfaces of 24 Themis and 1 Ceres. We present upper limits on the H 2 O production rate on these bodies derived using a search for [O I]6300Å emission.For Themis, the water production is less than 4.5 × 10 27 mol s −1 , while for Ceres our derived upper limit is 4.6 × 10 28 mol s −1 . The derived limits imply a very low fraction of the surface area of each asteroid is active (< 2 × 10 −4 ), though this estimate varies by as much as an or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…These values are an order of magnitude lower than those obtained by Jewitt & Guilbert-Lepoutre (2012) and McKay et al (2017). Like them, we conclude that such an ice-dust mixture percentage is entirely insufficient to explain the 3.1μm absorption.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…These values are an order of magnitude lower than those obtained by Jewitt & Guilbert-Lepoutre (2012) and McKay et al (2017). Like them, we conclude that such an ice-dust mixture percentage is entirely insufficient to explain the 3.1μm absorption.…”
Section: Discussioncontrasting
confidence: 60%
“…A more recent study (McKay et al 2017) presented the result of a non-detection following a search for gaseous H2O at optical wavelengths using the forbidden oxygen line at 6300.3 A˚ in line with similar observations performed on comets (McKay et al 2014(McKay et al , 2015. While no detection was made, an upper limit of Q(H2O) < 4.5 ×10 27 mol.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…We note that Themis was not found to be active by Jewitt and Guilbert-Lepoutre (2012), who suggested that if indeed present at its surface, water ice should be relatively clean and confined to a limited spatial extent, which was then confirmed by McKay et al (2017). Jewitt and GuilbertLepoutre (2012) observed Themis far from perihelion, however, which as discussed in Sect.…”
Section: Evidence For Water In Asteroidsmentioning
confidence: 67%
“…Two sets of telescopic observations suggest that Ceres has at least temporarily a water exosphere (A'Hearn & Feldman 1992;Küppers et al 2014). Despite negative results from follow-up observations with different observational facilities (Rousselot et al 2011;Roth et al 2016;McKay et al 2017;Roth 2018;Rousselot et al 2019), the production of the water exosphere on Ceres was the subject of many works (Tu et al 2014;Schorghofer et al 2016;Formisano et al 2016;Landis et al 2017;Villarreal et al 2017;Schorghofer et al 2017). Landis et al (2019) has analyzed the surface evolution based on the flux of impactors larger than 100m in diameter, however the effects of smaller meteoroids are yet to be assessed.…”
mentioning
confidence: 99%